Alfabetização de mulheres: a experiência da CNA-Nicarágua (1980) e do MOVA-SP (1989-1992) - Montero, Maria Júlia Alves Garcia (2018)
The present work analyzes two alphabetization programs that took place in Latin America: National Literacy Crusade "Heroes and Martyrs for the Liberation of Nicaragua" (CNA), held in Nicaragua in 1980, and the Youth and Adult Alphabetization Movement of São Paulo (MOVA-SP), carried out between the years of 1989 and 1992, in São Paulo, both organized based on the ideas of Paulo Freire, counting also with his direct participation. We have studied how, and if, the theme of feminism appears in the official documents of both programs, and whether the presence of this theme in these documents is due to the existence or not of a movement - or organization - of women in the country with the vanguard character, as Marta Harnecker conceptualizes. The concepts of gender, patriarchy and sexual division of labor, coined by authors such as Heleieth Saffioti, Carole Pateman, Iris Young, Danièle Kergoat, among others, were the theoretical basis of the present study. The research was conducted through documentary analysis. We studied official documents (political-pedagogical project, booklets, among others) of the two programs and analyzed a) if the subject of gender relations appeared; b) whether this appearance reinforced or questioned patriarchal gender relations; c) how it appeared, whether directly, indirectly, and in what context. We were able to conclude that the Nicaraguan documents have a greater presence of the theme, and that this is due to a more organized and centralized women's movement that, unlike the São Paulo movement - then fragmented and with a predominantly institutionalized activism - directly influenced alphabetization in the country. We do not affirm this, however, without reservations, since in both programs feminism appears as a very specific "subject", which reveals a difficulty in dealing with the theme of feminism transversally and even a theoretical difficulty in relation to it